Survey on electronic procurement implementation in Malaysia construction companies - 356627 Ng, Kim Aik (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2005